2021
DOI: 10.1101/2021.03.11.435033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary trajectories of three independent neo-sex chromosomes inDrosophila

Abstract: Dosage compensation (DC) on the X chromosome is a mechanism to counteract the deleterious effects by gene loss from the Y chromosome. However, DC cannot work efficiently if the X chromosome also degenerates. This indeed occurs in the neo-sex chromosomes in Drosophila miranda, where neo-X as well as neo-Y chromosomes are under accelerated pseudogenization. To examine the generality of this pattern, we investigated the evolution of two additional neo-sex chromosomes that independently emerged in D. albomicans an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Because either the fused or unfused version of the chromosome will only be present in males and male Drosophila do not undergo recombination, mutations immediately begin to accumulate through Hill-Robertson interference and other linkedselection processes (Charlesworth and Charlesworth 2000). In the genus Drosophila, autosomes have fused to sex chromosomes multiple independent times (Nozawa et al 2021): D. pseudoobscura (10 million years), D. miranda (1 million years; Bachtrog 2013), D. albomicans (0.24 million years; (Wei and Bachtrog), and D. americana (29 thousand years; (Vieira et al 2006). Neo-sex chromosomes formed by de novo sex chromosome fusions are rare and actually under-represented compared to autosomal fusions in Drosophila (Anderson et al 2020), and have never been discovered at their infancy before detectable divergence has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Because either the fused or unfused version of the chromosome will only be present in males and male Drosophila do not undergo recombination, mutations immediately begin to accumulate through Hill-Robertson interference and other linkedselection processes (Charlesworth and Charlesworth 2000). In the genus Drosophila, autosomes have fused to sex chromosomes multiple independent times (Nozawa et al 2021): D. pseudoobscura (10 million years), D. miranda (1 million years; Bachtrog 2013), D. albomicans (0.24 million years; (Wei and Bachtrog), and D. americana (29 thousand years; (Vieira et al 2006). Neo-sex chromosomes formed by de novo sex chromosome fusions are rare and actually under-represented compared to autosomal fusions in Drosophila (Anderson et al 2020), and have never been discovered at their infancy before detectable divergence has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq data were also downloaded from NCBI (Table S2 for detailed information). Gene annotation data were downloaded from Nozawa et al (2021) at the journal website (https://genome.cshlp.org/content/31/11/2069/suppl/DC1) as gff files and converted into gtf files.…”
Section: Genomes and Transcriptomes Of Three Trios Of Drosophila Speciesmentioning
confidence: 99%
“…One of such neo-sex chromosomes emerged in D. miranda by a fusion of the third chromosome with the Y about 1.1 Mya (Steinemann and Steinemann 1998;Bachtrog and Charlesworth 2002). Previous studies reported that the global DC via the MSL complex is already established on the neo-X chromosome (neo-X, hereafter) in D. miranda (Alekseyenko et al, 2013;Zhou et al, 2013), but the extent of the global DC is incomplete (Nozawa et al, 2018;Nozawa et al, 2021). In addition, these studies found that the DC on the neo-X-linked genes with the pseudogenized neo-Y-linked gametologs is greater than that on the neo-X-linked genes with the functional neo-Y-linked gametologs (Nozawa et al, 2018;Nozawa et al, 2021).…”
mentioning
confidence: 99%
“…Previous studies reported that the global DC via the MSL complex is already established on the neo-X chromosome (neo-X, hereafter) in D. miranda (Alekseyenko et al, 2013;Zhou et al, 2013), but the extent of the global DC is incomplete (Nozawa et al, 2018;Nozawa et al, 2021). In addition, these studies found that the DC on the neo-X-linked genes with the pseudogenized neo-Y-linked gametologs is greater than that on the neo-X-linked genes with the functional neo-Y-linked gametologs (Nozawa et al, 2018;Nozawa et al, 2021). This observation suggests that not only the global DC but also more localized DC (gene-by-gene DC, hereafter) operates on the neo-X by recognizing the functionality of neo-Y-linked genes in D. miranda, although the underlying mechanism and the immediacy of gene-by-gene DC remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation